THE PEDAGOGICAL CONTENT OF THE DEVELOPMENT OF SPEECH AND THINKING OF STUDENTS OF HIGHER EDUCATION INSTITUTIONS ON THE BASIS OF AN APPROACH - Abdullaeva Mavluda Aribovna (Scholar Express Journal, 2022)
This article describes the pedagogical essence of creative approaches to the development of speech and thinking of students of higher education institutions of the country on the basis of comparative analysis
Keywords: Creative approach; student activity; potential; educational modernization